1973
DOI: 10.1128/jb.113.3.1170-1176.1973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Esterases Produced by a Ruminal Bacterium Identified as Butyrivibrio fibrisolvens

Abstract: An obligately anaerobic ruminal bacterial isolate was selected from 18 tributyrin-degrading isolates and identified as Butyrivibrio fibrisolvens strain 53. The culture in late exponential phase contained enzymes which could be released by sonic disruption. These enzymes degraded substrates at a rate in the order 1-naphthyl acetate (NA) > 1-naphthyl butyrate > 1-naphthyl propionate but did not degrade 1-naphthyl palmitate or 1-naphthyl phosphate. The enzymes on NA were neither stimulated nor inhibited by CoCl2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…No radioactive undecyl acetate was detected by thin-layer radiochromatography when a hexane extract of the reaction mixture was chromatographed alone or with added nonradioactive undecyl acetate as carrier. DISCUSSION Citing only a few of numerous reports, multiple forms of esterases have been found in animals (2,24,25,27,31,44), plants (11,32), fungi (17,30,39), and bacteria (3,5,10,18,22,26,29). Throughout the course of the purification reported here, two esterase bands were always present.…”
Section: Resultssupporting
confidence: 50%
“…No radioactive undecyl acetate was detected by thin-layer radiochromatography when a hexane extract of the reaction mixture was chromatographed alone or with added nonradioactive undecyl acetate as carrier. DISCUSSION Citing only a few of numerous reports, multiple forms of esterases have been found in animals (2,24,25,27,31,44), plants (11,32), fungi (17,30,39), and bacteria (3,5,10,18,22,26,29). Throughout the course of the purification reported here, two esterase bands were always present.…”
Section: Resultssupporting
confidence: 50%
“…The missing differences in BH of LA between the PL and CE fractions could be concealed by the approximately 2% of free LA in the CE, which is biohydrogenated fast, and this may consequently cause an overestimation of the K M and V max values in the present study. The literature also seems consistent in the low esterase activity in the rumen, regardless of the sterol ester source, and it has been reported that the activity of the esterase enzymes was reduced when either 1‐naphthyl acetate (Lanz & Williams, ) was the source of sterol esters in in vitro condition or α‐tocopheryl acetate (Hymøller & Jensen, ) was the source of steroid in in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…Petersen and Jensen () have previously shown that in vitro BH differs between plant species. Studies on B. fibrisolvens esterase activity in rumen fluid have shown that enzyme activity declines with increasing chain length of the esterified FA (Hespell & O'Bryan‐Shah, ; Lanz & Williams, ). Tocopherol esters seem not to be hydrolyzed in the rumen of dairy cows (Hymøller & Jensen, ) and the same is hypothesized for more complex FA esters such as sterol esters.…”
Section: Introductionmentioning
confidence: 99%
“…Although these enzymes have long been studied, a physiological function has only recently been suggested for some of them (Mentlein et al, 1985 ;Varki et al, 1986). Progress has been made in the last few years on elucidating the roles of carboxylesterases from mammalian sources (Mentlein et al, 1987;Long et al, 1988;Ozols, 1989;Korza and Ozols, 1988), but much less information is available on bacterial carboxylesterases, which have also been demonstrated to show large heterogeneity (Lanz and Williams, 1973;Goullet and Picard, 1990 and references therein and this work). Detailed molecular studies are necessary to elucidate the evolutionary relationships of these enzymes.…”
mentioning
confidence: 94%